Insurance fraud casebook : paying a premium for crime - Wells, Joseph T. (John Wiley & Sons, Inc., 2013)
Real case studies on insurance fraud written by real fraud examiners Insurance Fraud Casebook is a one-of-a-kind collection consisting of actual cases written by fraud examiners out in the field. These cases were hand selected from hundreds of submissions and together form a comprehensive picture of the many types of insurance fraud-how they are investigated, across industries and throughout the world. Entertaining and enlightening, the cases cover every type of insurance fraud, from medical fraud to counterfeiting. Each case outlines how the fraud was engineered, ho.